Fluidic Platforms Incorporating Photo-Responsive Soft-Polymers Based on Spiropyran: From Green Synthesis to Precision Flow Control - Pandurangan, Komala; Barrett, Ruairi; Diamond, Dermot; McCaul, Margaret (Frontiers in Materials, 2021)
In this paper, we describe how to create simple fluidic systems incorporating soft polymer actuator valves, that can provide highly precise control of flow rates in fluidic channels as an example of a 4D-materials based platform. The particular approach we describe employs photoresponsive gels that swell/contract via a light stimulus, enabling flow behavior to be controlled from outside the fluidic platform in a completely remote and non-contact manner. An improved synthesis of the spiropyran molecular photoswitch that delivers high yields (77%) using scalable green chemistry is described, along with details on how to build the valve structures in custom designed sites within the fluidic system. Fabrication of a demonstrator fluidic system incorporating up to four valves is described, along with electronics and in-house developed PID control software for achieving precise control of flow in the channels using LEDs. The resulting system demonstrates an innovative approach to microfluidics that offers scalability in terms of the number of polymer actuators along with wide variability of actuator form and function.